Lean Manufacturing Production Method using the Change Management Approach to Reduce Backorders at SMEs in the Footwear Industry in Peru - Dextre-Del-Castillo, D. (2020)
This article proposes a production method that aims to increase the manufacturing capacity of a footwear small- and medium-sized enterprise (SME) to reduce backorders. Therefore, an assessment is carried out and delays in production processes, excess product transport time, defective products, and inefficient work methods are identified. This article proposes designing a Lean manufacturing method using the change management approach, whose methodology is composed of six phases. In phase 0, change management is carried out; in phase 1, the company's current situation is reviewed using the Value Stream Mapping (VSM); in phase 2, the work area is reorganized (implementing SLP and 5S); in phase 3, production is balanced (implementing Line Balancing); in phase 4, continual improvement is established using the Kaizen tool; and finally, in phase 5, the results are evaluated. Through validation, it was possible to confirm that Lean manufacturing tools along with change management increased order deliveries by 82%.